FORECASTING KONSUMSI LISTRIK DI INDONESIA - Ridhani Ridhani; Muhammad Ilhamsyah Siregar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2021)
ABSTRACTThis study aims to determine the projection of electricity consumption needs in Indonesia in 2020 to 2024. This study uses the ARIMA model approach by using secondary data, namely electricity consumption data measured in KWh per capita units in Indonesia from 1971 to 2019, namely as much as 48 records. The results of this study indicate that the best model of electricity consumption projection is the ARIMA (1,1,0) model. Based on the results experiencing low fluctuation. The percentage value for 2020 to 2024 only ranges from 1.85 to 1.89% from the previous year. Because, every year there is an increase in electricity consumption in Indonesia, to minimize the risks that may occur in the future, PT PLN (Persero) must continue to increase productivity and increase the supply of electricity such as adding new transmissions, renewable energy and others to meet electricity consumption in the future. country. Keywords: Projection, ARIMA model, electricity consumption.